Beginning teachers’ conceptions of competency: implications to educational policy and teacher education in Malaysia - Goh, Pauline Swee Choo; Wong, Kung Teck (Educational research for policy and practice, 2014)
When any innovations or measurement procedures are introduced into the education system to improve or judge the quality of its teaching force, beginning teachers often have to adapt to these new concepts of what constitute a high quality teaching. This article contends that these new concepts neither necessarily match beginning teachers’ own conceptions about their own competency nor has it given beginning teachers a chance to be heard. This study provides an opportunity for beginning teachers’ ‘voices’ to be heard through phenomenography which is an interpretive research approach to discover what beginning teachers in Malaysia conceive and understand as competence in relation to what they do every day as teachers. The main finding of this study is the key role played by beginning teachers’ conceptions of competency which has provided strong implications for educational policies and teacher education. The findings suggest that teachers need to be represented in any quality improvement measures. Careful attention should also be paid to the school systems and to teacher training programmes to support and encourage teachers in their professional growth as competent teachers.